Dynamic finite element analysis of a robotic arm for electronic devices transportation: design and simulation - Shaarany Chelliah (2024)
In the realm of industrial automation, robotics plays a significant and central role. robotic solutions are incorporated into cyber physical systems and production systems to automate industrial operations. The already-high level of manufacturing productivity will be increased by this since the production cycle time and total cost will be lowered. In this study, the modelling and simulation of a robotic arm for use in transporting printers are discussed. Under a variety of stresses and with many kinds of materials, the finite element analysis (FEA) was performed with the help of Solidworks 2019. (AISI304, cast carbon steel, aluminum alloy 1060, malleable cast iron, and AISI1020). The findings illustrate several types of materials, load of printers and shape of the robotic arm, each with its own distinct set of mechanical characteristics. As a result of the strain, stress, and displacement distributions, it can be deduced that the robotic arm will be able to conduct the grasping, handling, and assembly activities with a high degree of precision and accuracy throughout the transportation processes. By selecting the appropriate materials, one may facilitate the production of goods of superior quality in a manner that is both fast and inexpensive.